bonjour,
x^2- 5x- 6= 0 au collège je vois pas
4x^2- 16 = (x-2)^2 =
(4x²-16)-(x-2)² = a²-b² qu'on factorise(a-b)(a+b)
(2x-4-x+2)(2x-4+x-2) =0
(x-2)(3x-6) =0
3(x-2)(x-2) = 0
3(x-2)² = 0
x-2 = 0
x = 2
4x^2- 9= (2x-3)(1-x)
(4x²-9)-(2x-3)(1-x) =
(2x-3)(2x+3)-(2x-3)(1-x) = 0
(2x-3)(2x+3-1+x) = 0
(2x-3)(3x+2) = 0
2x-3 =0
2x = 3
x =3/2
3x+2 = 0
3x =-2
x =-2/3
3x^2-9= (x-√3) t'es sur de (x-√3) ?
(3x²-9)-(x-√3) =
(x√3-3)(x√3+3)-(x-√3)
9x^2- 5= x(3x-√5)
(3x-√5)(3x+√5)-x(3x-√5) =0
(3x-√5)(3x+√5-x) = 0
(3x-√5)(2x+√5) = 0
3x-√5 = 0
3x = √5
x =√5/3
2x+√5 = 0
2x =-√5
x =-√5/2